Clinical use of intracoronary imaging. Part 1: guidance and optimization of coronary interventions. An expert consensus document of the European Association of Percutaneous Cardiovascular Interventions. (22nd May 2018) - Räber, Lorenz; Mintz, Gary S; Koskinas, Konstantinos C; Johnson, Thomas W; Holm, Niels R; Onuma, Yoshinubo; Radu, Maria D; Joner, Michael; Yu, Bo; Jia, Haibo; Meneveau, Nicolas; de la Torre Hernandez, Jose M; et al.
Abstract: This Consensus Document is the first of two reports summarizing the views of an expert panel organized by the European Association of Percutaneous Cardiovascular Interventions (EAPCI) on the clinical use of intracoronary imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT). The first document appraises the role of intracoronary imaging to guide percutaneous coronary interventions (PCIs) in clinical practice. Current evidence regarding the impact of intracoronary imaging guidance on cardiovascular outcomes is summarized, and patients or lesions most likely to derive clinical benefit from an imaging-guided intervention are identified. The relevance of the use of IVUS or OCT prior to PCI for optimizing stent sizing (stent length and diameter) and planning the procedural strategy is discussed. Regarding post-implantation imaging, the consensus group recommends key parameters that characterize an optimal PCI result and provides cut-offs to guide corrective measures and optimize the stenting result. Moreover, routine performance of intracoronary imaging in patients with stent failure (restenosis or stent thrombosis) is recommended. Finally, strengths and limitations of IVUS and OCT for guiding PCI and assessing stent failures and areas that warrant further research are critically discussed.